The Status of Criminological Theories in Turkey: A Brief Account - Özbay, Özden (International Journal of Criminology and Sociology, 2016)
The aim of this study is to evaluate the status of criminological theories in Turkey and to present some recommendations to follow in the future. Unfortunately, some sub-disciplines in social sciences in Turkey have been relatively less developed. This is especially valid for criminology or sociological studies of crime. More relavant to this paper, there have been a limited number of tests of western-originated criminological theories in Turkey. It is suggested that Turkish scholars test all the existing criminological theories in the context of Turkey and, more importantly, tend to develop criminological theories that reflect Turkish realities.